2020
DOI: 10.1200/go.20.00202
|View full text |Cite
|
Sign up to set email alerts
|

Reliance on Self-Medication Increase Delays in Diagnosis and Management of GI Cancers: Results From Nepal

Abstract: PURPOSE Patients with GI cancers in Nepal often present with advanced disease and poor outcomes. The purpose of the study was to determine the time to presentation, diagnosis, and treatment of GI cancer and the baseline factors that may be associated with delays. PATIENTS AND METHODS An institutional review board–approved study was performed in Kathmandu, Nepal, from July 2018 to June 2019. Patients with newly diagnosed GI cancers were asked to fill out a standardized questionnaire. Baseline factors such as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Herbal medicines are frequently used by cancer patients, ranging in prevalence from 19.7% to 69% [ 37 , 38 , 39 , 40 ], and patients taking herbal medicines have lower overall survival at 3 and 5 years than patients not taking herbal medicines [ 37 ], which underlines the unknown safety of these behaviors and self-medication practices. Moreover, self-medication practices can delay cancer diagnosis (e.g., gastrointestinal cancer [ 41 , 42 ], hematological malignancies [ 43 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicines are frequently used by cancer patients, ranging in prevalence from 19.7% to 69% [ 37 , 38 , 39 , 40 ], and patients taking herbal medicines have lower overall survival at 3 and 5 years than patients not taking herbal medicines [ 37 ], which underlines the unknown safety of these behaviors and self-medication practices. Moreover, self-medication practices can delay cancer diagnosis (e.g., gastrointestinal cancer [ 41 , 42 ], hematological malignancies [ 43 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they also found that despite abdominal pain being the most common help‐seeking trigger, help‐seeking was often delayed due to its attribution to ‘normal’ indigestion (Humphrys et al, 2020; Mills et al, 2017). An Italian and Nepalese study reported self‐medication to treat indigestion, which was associated with longer time to presentation, diagnosis and treatment (Dulal et al, 2020; Gobbi et al, 2013). In our study, however, patients tried alleviating their symptoms by changing their diet rather than taking medication.…”
Section: Discussionmentioning
confidence: 99%
“…However, like other developing countries, out-of-pocket (OOP) expenditure is the dominant source of health financing in Nepal and Nigeria. More than 11% of Nepalese spend 10% of their total expenses for health [ 38 ], where 1.67% of the population is pushed below the poverty line of PPP$ 1.90 per capita per day [ 39 ]. Generally, 70% of the Nepalese use OOP payment for their health care [ 40 ]; however patients with cancer are beginning to receive help as the Nepalese government is currently providing financial assistance of up to NRs 100,000 (Euro 735.41, USD 830.17 exchange rate as of June 9, 2020) per person for cancer treatment under a scheme to support impoverished citizens [ 41 ].…”
Section: Lack Of Fundsmentioning
confidence: 99%